Pneumosinus Dilatans: A Case Report and Bone Analysis of a Rare Observation of its Relationship with Meningioma - Lopes, Gabriel de Assis; Silva, Letícia de Mello; Guimarães, Alexandre Baldasserini; de Freitas, Paulo Antônio; Cavalcante, Lívia Barreira; Stamm, Aldo Eden Cassol; Vellutini, Eduardo de Arnaldo Silva (Brazilian Journal of Case Reports, 2026)
Pneumosinus dilatans (PD) is an abnormal expansion of the paranasal sinuses, frequently associated with anterior skull base meningiomas. Despite its potential clinical significance, the etiology remains unclear, with theories ranging from mechanical obstruction to biochemical stimulation. We report a case of a 30-year-old male with a tuberculum sellae meningioma who developed sphenoid PD after years of surveillance, concurrent with continuous tumor growth. The patient underwent successful endoscopic resection, with histopathology confirming a World Health Organization (WHO) grade I meningioma infiltrating bone. This temporal association supports the theory that PD arises from active, tumor-induced bone remodeling rather than obstructive mechanisms. PD should be recognized as a significant radiographic marker of underlying meningioma activity, warranting thorough investigation and influencing management decisions.